Some characteristics of sequences of iterations with random perturbations - Dorogovtsev, A. A.; Дороговцев, А. А.; Дороговцев, А. А. (Institute of Mathematics, NAS of Ukraine, 1996)
For a sequence of random iterations, we study the set of partial limits and the frequency of visiting their neighborhoods.